Comparative X-Ray Crystallographic Studies Of Systemic Fungicide Hexaconozole And Tricyclazole - DR JYOTSNACHAUHAN,; ASHISH KUMAR SHARMA, (International Journal of Pharma and Bio Sciences, 2012)
The activity of fungicides is intimately related to its chemical structure. Knowledge about the chemical structure of a chemical is useful for the synthesis of new compounds with more specific actions and fewer adverse reactions, to increase/decrease the duration of action of the original fungicide or to get a more potent compound, to restrict the action to a specific system of the plant body and to reduce the adverse reactions, toxicity and other disadvantages associated. We can understand the basic chemical groups responsible for fungicidal action. A systemic fungicide is defined as systemic fungi toxic compound that controls a fungus pathogen remote from the point of application and that can be detected or identified 2.These compounds are absorbed by the plant and get translocated within it, thus providing protection as well as eradicating already established infection.